Canjerê: uma performance cartográfica em patrimônio cultural, educação e africanidades - Gama, Alessandra Regina (2016)
This study aimed present the máster’s dissertation named Canjerê: uma performance cartográfica em patrimônio cultural, educação e africanidades, held in the Postgraduate Program in Education of the Federal University of São Carlos (UFSCar). This research is proposed to follow the process of an experience lived by individuals and black cultural practices, which resulted in creation of Instituto Baobá de Cultura e Arte – o Ibaô – in Campinas (SP). The movement of this research reveals an experience as possible against what is hegemonic tax as only true culture, from the practice of Capoeira and other black cultural expressivity. Based on the invisibility of issue of black people, this process offers clues to the construction of aternatives that break the dominant models, weaving reflections on the social hostilities that affect the uniqueness and identity construction centered africanities and as the prospect of knowledge of ecology can contribute to the construction of new existential territories.